Answer: A(2,3)
Explanation:
To solve the system of equations;
y=-1/2x+4 and y = 2x – 1
y=-1/2x+4 ----------(1)
y = 2x – 1 -----------(2)
Lets substitute equation 2 in equation 1
2x - 1 = -1/2x+4
Collect like term
(We move the x variables from the right -hand side of the equation to the right-hand side of the equation to the right-hand-side of the equation and then move the constants to the right-hand side of the equation)
2x + 1/2x = 4 + 1
5x/2 = 5
To get the value of x, we will multiply both-side of the equation by 2/5
5x/2 × 2/5 = 5 × 2/5
(On the left-hand side of the equation, the 5/2 will cancel out the 2/5 leaving us with x and on the right-hand side of the equation 5 will cancel out 5 leaving us with 2)
x = 2
Substitute x =2 in equation (2)
y = 2x - 1
y = 2(2) - 1
y = 4 -1
y =3
The solution to the system of the equations is x=2 and y=3
Therefore the answer is A(2,3)